Impact of Nutrient Management on Wheat/Vegetable Yields and the Fate of 15N-Labeled Fertilizer in the Yangtze River Basin - Wang, Sen; Yang, Lin Sheng; Liao, Shi Peng; Sun, Bo; Shi, Xiao Jun; Lu, Jian Wei; Guo, Shi Wei; Shen, Jian Bo; Zhang, Fu Suo; Goulding, Keith; Liu, Xue Jun (Frontiers in Environmental Science, 2022)
The Yangtze River Basin (YRB) crosses three economic zones and major agricultural regions of eastern, central and western China. Increasing non-point source pollution, caused by excessive nitrogen (N) inputs to farms, is one of the main causes of water contamination in the YRB. To improve N fertilizer use efficiency we conducted a field experiment using 15N-labeled urea at three sites located in upstream, midstream and downstream regions of the YRB to evaluate the impacts of improved fertilizer management on crop yield, fertilizer N recovery and losses in three crop rotations: rice-wheat (RW), rice-vegetable (RV) (tuber mustard at Jiangjin (Chongqing), cabbage at Shayang (Hubei) and savoy cabbage at Rugao (Jiangsu)) and maize-wheat (MW). Applying only 50% of the traditional application of N and P fertilizer maintained the wheat yield at Jiangjin and Shayang and savoy cabbage yield at Rugao. However, it caused a 27% reduction of the wheat yield at Rugao. The 15N recovery showed that 27% of the fertilizer N was retained in the soil and that 25% less fertilizer N was lost to the environment compared to the traditional fertilizer application. Improved fertilizer management would reduce the environmental cost of farming in the YRB, but with some consequences to winter crop yields.